Apurinic/apyrimidinic endonuclease 1, p53, and thioredoxin are linked in control of aging in C. elegans - Schlotterer, Andrea; Hamann, Andreas; Kukudov, Georgi; Ibrahim, Youssef; Heckmann, Britta; Bozorgmehr, Farastuk; Pfeiffer, Michael; Hutter, Harald; Stern, David; Du, Xueliang; Brownlee, Michael; Bierhaus, Angelika; et al. (Aging cell, 2010)
Deletions in mitochondrial DNA (mtDNA) accumulate during aging. Expression of the Caenorhabditis elegans apurinic/apyrimidinic endonuclease 1 (APE1) ortholog exo-3, involved in DNA repair, is reduced by 45% (P < 0.05) during aging of C. elegans. Suppression of exo-3 by treatment with RNAi resulted in a threefold increase in mtDNA deletions (P < 0.05), twofold enhanced generation of reactive oxygen species (ROS) (P < 0.01), distortion of the structural integrity of the nervous system, reduction of head motility by 43% (P < 0.01) and whole animal motility by 38% (P < 0.05). Suppression of exo-3 significantly reduced life span: mean life span decreased from 18.5 ± 0.4 to 15.4 ± 0.1 days (P < 0.001) and maximum life span from 25.9 ± 0.4 to 23.2 ± 0.1 days (P = 0.001). Additional treatment of exo-3-suppressed animals with a mitochondrial uncoupler decreased ROS levels, reduced neuronal damage, and increased motility and life span. Additional suppression of the C. elegans p53 ortholog cep-1 in exo-3 RNAi-treated animals similarly decreased ROS levels, preserved neuronal integrity, and increased motility and life span. In wild-type animals, suppression of cep-1, involved in downregulation of exo-3, increased expression of exo-3 without a significant effect on ROS levels, preserved neuronal integrity, and increased motility and life span. Suppression of the C. elegans thioredoxin orthologs trx-1 and trx-2, involved in the redox chaperone activity of exo-3, overrides the protective effect of cep-1 RNAi treatment on neuronal integrity, neuronal function, mean and maximum life span. These results show that APE1/EXO-3, p53/CEP-1, and thioredoxin affect each other and that these interactions determine aging as well as neuronal structure and function.
Gesehen am 13.06.2023